Hunting management: the need to adjust predictive models to field observations - Renoux, Francois; de thoisy, Benoit (Ethnobiology and Conservation, 2016)
Wild meat is a major protein supply for numerous traditional communities worldwide, but impacts ecological processes and consequently challenges the relevance and suitability of adequate monitoring of the sustainability of harvests. In this study we discuss the classic models of theoretical ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œmaximum sustainable offtakeÃƒÂ¢Ã¢â€šÂ¬Ã‚Â and propose new considerations on sustainable harvest thresholds. The study focuses on French Guiana, northern Amazonia, on four sites harvested by three communities (Amerindian, Creole, and Hmong), mainly for subsistence purposes. We explored how factors related to the number of hunters, the harvested areas, and the surface area hunted, and measured how fauna abundance generates uncertainties on models and increases the errors on sustainable thresholds. Biased or incomplete ethnologic surveys, as well as local and temporal variations in game species density could lead to considerable underestimation of harvests. We proposed a set of corrections that, once applied to theinput variables of the offtake model, could limit the risk of erroneous assessment of sustainability thresholds.